2022
DOI: 10.1111/jfbc.14229
|View full text |Cite
|
Sign up to set email alerts
|

Comparative bioactivity profile of phospholipids from three marine byproducts based on the zebrafish model

Abstract: Phospholipids (PLs) are important components of physiological metabolism in animals and plants, and they have been widely used in clinical treatment, cosmetics, and industry. With the development of marine resources, marine PLs rich in polyunsaturated fatty acids have attracted increasing attention. As important marine resources, shrimp heads (SH), codfish roe (CR), and squid gonads (SG) contain a high PL content.The antithrombotic, antistroke, anti-inflammatory, pro-angiogenic, and cardioprotective activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Finally, it is important to highlight that, more than just a potential to display beneficial effects based on their composition, some lipid fractions from marine animal co-products have in fact been ascribed interesting biological activities. Phospholipid extracts from shrimp heads, codfish roe, and squid gonads were tested for their antithrombotic, antistroke, anti-inflammatory, pro-angiogenic, and cardioprotective activities, with promising results [230]. Another study highlighted the anti-inflammatory activities of extracts from gloomy octopus (Octopus tetricus) viscera, squid (Sepioteuthis australis) heads, Australian sardine (Sardinops sagax) viscera/heads, salmon (S. salar) heads, and school prawn (Penaeus plebejus) viscera/heads [169].…”
Section: The Value Of Marine Animal Co-product Lipids For Various Ind...mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is important to highlight that, more than just a potential to display beneficial effects based on their composition, some lipid fractions from marine animal co-products have in fact been ascribed interesting biological activities. Phospholipid extracts from shrimp heads, codfish roe, and squid gonads were tested for their antithrombotic, antistroke, anti-inflammatory, pro-angiogenic, and cardioprotective activities, with promising results [230]. Another study highlighted the anti-inflammatory activities of extracts from gloomy octopus (Octopus tetricus) viscera, squid (Sepioteuthis australis) heads, Australian sardine (Sardinops sagax) viscera/heads, salmon (S. salar) heads, and school prawn (Penaeus plebejus) viscera/heads [169].…”
Section: The Value Of Marine Animal Co-product Lipids For Various Ind...mentioning
confidence: 99%
“…Lipids from co-products of marine animals may also be appealing to the fields of pharmacology and drug development. As previously mentioned, phospholipid extracts from co-products derived from fish, crustaceans, and mollusks have been shown to display interesting biological activities, and have therefore been suggested as possible targets for pharmacological and clinical studies and development, namely in the context of inflammatory and cardiovascular diseases [230]. Moreover, phospholipids have also attracted interest as drug delivery systems on the basis of their excellent biocompatibility and amphiphilicity [259,260].…”
Section: The Value Of Marine Animal Co-product Lipids For Various Ind...mentioning
confidence: 99%
“…Collectively, these studies further highlight the role that both PAF and its metabolism play in atherosclerosis and the role that future fish PL-based therapeutics may play in the battle against CVD. Indeed, multiple studies have demonstrated potential antiplatelet properties of fish oil PLs in vitro against PAF and various platelet agonists [137][138][139][150][151][152] and in various models of CVD in vivo [145,153]. However, it should be noted that PL sources characterized by lower levels of n-3 PUFAs such as dairy and meat also exhibit antiplatelet effects to a similar extent [21,154,155], indicating the promise of developing PL-based therapeutics generally.…”
Section: Marine Oil Polar Lipids: Innovations and Human Healthmentioning
confidence: 99%
“…Finally, it is important to highlight that, more than just a potential to display beneficial effects based on their composition, some lipid fractions from marine animal co-products have in fact been ascribed interesting biological activities. Phospholipid extracts from shrimp heads, codfish roe, and squid gonads were tested for their antithrombotic, anti-stroke, anti-inflammatory, pro-angiogenic, and cardioprotective activities with promising results [214]. Another study highlighted the antiinflammatory activities of extracts from gloomy octopus (Octopus tetricus) viscera, squid (Sepioteuthis australis) heads, Australian sardine (Sardinops sagax) viscera/heads, salmon (S. salar) heads and school prawn (Penaeus plebejus) viscera/heads and [152].…”
Section: The Value Of Marine Animal Co-product Lipids For Human Healthmentioning
confidence: 99%
“…Lipids from co-products of marine animals may also be appealing to the fields of pharmacology and drug development. As previously mentioned, phospholipid extracts from co-products derived from fish, crustaceans and mollusks have been shown to display interesting biological activities, and therefore suggested as possible targets for pharmacological and clinical studies and development, namely in the context of inflammatory and cardiovascular diseases [214]. Moreover, phospholipids have also attracted interest as drug delivery systems on the basis of their excellent biocompatibility and amphiphilicity [239,240].…”
Section: The Value Of Marine Animal Co-product Lipids For Industrymentioning
confidence: 99%